Insights Into Mount Etna December 2018 Eruption From Joint Inversion of Deformation and Gravity Data. Issue 16 (24th August 2020) - Chauhan, Mahak Singh; Cannavó, Flavio; Carbone, Daniele; Greco, Filippo
Abstract: We present results of the joint analysis of ground deformation and superconducting gravity data encompassing Etna's December 2018 eruption. The horizontal ground deformation points to a mechanism of dike opening. Accordingly, we consider forward analytical models describing the effects of a tensile dislocation and use two data inversion approaches, based on heuristic and probabilistic methods. The observed changes can be explained assuming the intrusion of a fluid lighter than bubble‐free magma, along a dike‐like structure. However, the poor fit to the vertical deformation and the discrepancy between bulk volume increase, deduced by the data inversion (some tens of millions of m 3 ), and volume emitted through effusive activity (∼1 × 10 6  m 3 ) suggest that a more complex mechanism led to the eruption, involving partial inelastic accommodation of the strain and the formation of void space through increase in the fracturing rate of the medium. Plain Language Summary: Volcanic eruptive activity is often preceded and accompanied by ground deformation and changes in the local gravity field, in turn driven by the dynamics of magma in the plumbing system of the volcano. The analysis of deformation and gravity data can provide unique information on intrusive events leading to paroxysmal activity. Here, we use ground deformation andgravity data to shed new light on the December 2018 eruption of Etna, which ensued from fissures in the upper SE flank of the volcano. Data inversion indicates that the eruption was fed by the intrusion of light magma along a sheet‐like structure, cutting the SE sector of the volcanic edifice. However, some features of the available observations suggest that the mechanism, which led to the eruptive event involved, besides the elastic deformation of the volcanic edifice in response to the magma intrusion, inelastic accommodation of the strain, and formation of dry fractures. Key Points: We perform the joint analysis of deformation and gravity data encompassing the December 2018 eruption of Etna Time series from superconducting gravimeters are used to gain insight into the processes associated with a volcanic eruption A complex mechanism led to the eruption, involving inelastic accommodation of the strain and formation of dry fractures